Should oral contraceptive pills be available without a prescription? A systematic review of over-the-counter and pharmacy access availability - James Kiarie; Ping Teresa Yeh; Caitlin E Kennedy; Lianne Gonsalves; Hussain Jafri; Mary Eluned Gaffield; Manjulaa L Narasimhan (BMJ Global Health)
Introduction Making oral contraceptives (OC) available over the counter (OTC) could reduce barriers to use. To inform WHO guidelines on self-care interventions, we conducted a systematic review of OTC availability of OCs.Methods We reviewed data on both effectiveness and values and preferences surrounding OTC availability of OCs. For the effectiveness review, peer-reviewed articles were included if they compared either full OTC availability or pharmacist-prescribing (behind-the-counter availability) to prescription-only availability of OCs and measured an outcome of interest. For the values and preferences review, we included peer-reviewed articles that presented primary data (qualitative or quantitative) examining people’s preferences regarding OTC access to OCs. We searched PubMed, CINAHL, LILACS and EMBASE through November 2018 and extracted data in duplicate.Results The effectiveness review included four studies with 5197 total participants. Two studies from the 2000s compared women who obtained OCs OTC in Mexico to women who obtained OCs from providers in either Mexico or the USA. OTC users had higher OC continuation rates over 9 months of follow-up (adjusted HR: 1.58, 95 % CI 1.11 to 2.26). One study found OTC users were more likely to report at least one WHO category 3 contraindication (13.4% vs 8.6%, p=0.006), but not category 4 contraindications; the other study found no differences in contraindicated use. One study found lower side effects among OTC users and high patient satisfaction with both OTC and prescription access. Two cross-sectional studies from the 1970s in Colombia and Mexico found no major differences in OC continuation, but some indication of slightly higher side effects with OTC access. In 23 values and preference studies, women generally favoured OTC availability. Providers showed more modest support, with pharmacists expressing greater support than physicians. Support was generally higher for progestogen-only pills compared with combination OCs.Conclusion A small evidence base suggests women who obtain OCs OTC may have higher continuation rates and limited contraindicated use. Patients and providers generally support OTC availability. OTC availability may increase access to this effective contraceptive option and reduce unintended pregnancies.Systematic review (PROSPERO) registration number CRD42019119406.